2015
DOI: 10.1177/1359105315609087
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mental health outcomes associated with prior food insecurity among young adults

Abstract: Following a biopsychosocial model of food insecurity, this study examined differences in physical health and mental health outcomes among young adults ( N = 98) with and without a history of food insecurity. Young adults with a history of food insecurity had higher average levels of body mass index, waist-to-height ratio, depressive symptoms, stress, and disordered eating scores than individuals with no history of food insecurity. No differences were found with symptoms of anxiety. Future research should exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 80 publications
2
40
0
Order By: Relevance
“…Other recent studies have used this framework to examine or define the link between food insecurity risk factors and specific physical or mental health outcomes. 31,32 Figure 1 shows a modified model of the framework with descriptions of key components. Components are divided into the social context of food access, representing the risk factors for food insecurity, and the experiential dimension of food access, representing the consequences of food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have used this framework to examine or define the link between food insecurity risk factors and specific physical or mental health outcomes. 31,32 Figure 1 shows a modified model of the framework with descriptions of key components. Components are divided into the social context of food access, representing the risk factors for food insecurity, and the experiential dimension of food access, representing the consequences of food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…A third study also found increased BMI associated with past exposure to food insecurity. [31] While these studies shed important light on the issue, studies exploring the temporal relationship between food insecurity, obesity, and dietary patterns remain limited.…”
Section: Food Insecurity and Obesitymentioning
confidence: 99%
“…The studies used a diverse group of questionnaires for measuring FIS and anxiety, with one study directly measuring cortisol levels. The effect of FIS on anxiety was shown in preschool children (51), pregnant women (52,53), general public visiting the emergency department (ED)(54), diabetic patients (55,56), Hispanic adults (57), and college freshmen (58).…”
Section: Anxietymentioning
confidence: 99%
“…The mechanism between food insecurity and anxiety is straightforward: members of the family worry about the household's family food supply (58,59). This is not only unfortunate for the obvious impact on the patient and family, but to society in general, since anxiety has a well-known economic burden associated with both medical and general productivity costs(60).…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation